ODIN: High Clustering Strength of Protoclusters at Cosmic Noon - Vandana Ramakrishnan; Kyoung-Soo Lee; Nicole Firestone; Eric Gawiser; Maria Celeste Artale; Caryl Gronwall; Lucia Guaita; Ho Seong Hwang; Sang Hyeok Im; Woong-Seob Jeong; Seongjae Kim; Ankit Kumar; et al. (The Astrophysical Journal)
The One-hundred-deg ^2 DECam Imaging in Narrowbands (ODIN) survey is carrying out a systematic search for protoclusters during Cosmic Noon, using Ly α -emitting galaxies (LAEs) as tracers. Once completed, ODIN aims to identify hundreds of protoclusters at redshifts of 2.4, 3.1, and 4.5 across seven extragalactic fields, covering a total area of up to 91 deg ^2 . In this work, we report the high clustering strength of the ODIN protoclusters, determined via measurements of their cross-correlation with LAEs. Our sample consists of 150 protocluster candidates at z = 2.4 and 3.1, identified in two ODIN fields with a total area of 13.9 deg ^2 . At z = 2.4 and 3.1, the inferred protocluster biases are $6.{6}_{-1.1}^{+1.3}$ and $6.{1}_{-1.1}^{+1.3}$ , corresponding to mean halo masses of $log\langle M/M_{\odot }\rangle =13.5{3}_{-0.24}^{+0.21}$ and $12.9{6}_{-0.33}^{+0.28}$ , respectively. By the present day, these protoclusters are expected to evolve into virialized galaxy clusters with a mean mass of ∼10 ^14.5 M _⊙ . By comparing the observed number density of protoclusters to that of halos with the same measured clustering strength, we find that the completeness of our sample is of order unity. Finally, the similar descendant masses derived for our samples at z = 2.4 and 3.1, assuming that the halo number density remains constant, suggest that they represent similar structures observed at different cosmic epochs. As a consequence, any observed differences between the two samples can be understood as redshift evolution. The ODIN protocluster samples will thus provide valuable insights into the cosmic evolution of cluster galaxies.